The Law and Economics of Self-Dealing - Djankov, Simeon; La Porta, Rafael; Lopez-de-Silanes, Florencio; Shleifer, Andrei (2012)
We present a new measure of legal protection of minority shareholders against expropriation by corporate insiders: the anti-self-dealing index. Assembled with the help of Lex Mundi law firms, the index is calculated for 72 countries based on legal rules prevailing in 2003, and focuses on private enforcement mechanisms, such as disclosure, approval, and litigation, that govern a specific self-dealing transaction. This theoretically grounded index predicts a variety of stock market outcomes, and generally works better than the previously introduced index of anti-director rights.